PSYCHOLOGICAL WELL-BEING OF THE DYAD IN MODERN STUDIES - Shipova , N. S. (Արդի հոգեբանություն, 2019)
The psychological well-being of a dyad is an important factor determining its viability and the satisfaction of partners in relationships. However, at present, there are few scientific researches of this phenomenon. More attention is paid to the psychological well-being of the individual subject. We study this phenomenon in theoretical and empirical aspects in our study. The empirical evidence of the study is 20 couples. Each of them is in close relationships of at least 2 years. The average age of partners is 35.5 years. The research tools used include test, projective techniques and semi-structured phenomenological interview. We considered aspects of the subjective well-being of each of the partners, ideas about difficult life situations, psychological climate in the dyad, satisfaction with relationships, coincidence of internal attitudes for close relationships, efficiency of individual and dyadic coping As indicators of the subjective well-being of the dyad.